http://psyjournals.ru/files/89552/autism_2017_n4_don.pdf - Hot'ko S.V (Moscow State University of Psychology and Education, 2017)
Large area of Leningrad Oblast and scatteredness of residences of children with autism spectrum disorders complicated the work on formation of the model of comprehensive support for ASD children in region. Stages of work are described. Institutions and organizations, which are involved in the process of the formation of the model of comprehensive support for children and their families, are listed.